Lightweight design of peanut sowing machine frame based on finite element analysis - Yu, Yan; Diao, Linsong; Wang, Dongwei; Wang, Jiasheng; Wang, Xiaomin; Tan, Xiaozhi; Yi, Dazhi (International Journal of Agricultural and Biological Engineering, 2023)
In order to reduce the weight and energy consumption of the whole machine against the heavy mechanical structure and excessive strength redundancy in current small-scale peanut seeders with one ridge and two rows, a finite element model of the frame was established and the static finite element analysis and modal analysis were conducted with ANSYS Workbench. Sensitivity analysis that focuses on the size of intermediate support beams and other components was performed so as to set up a multi-objective optimization model. Then a size optimization and multi-objective optimization collaborative scheme was adopted so that the target was optimized by the Seagull Optimization Algorithm (SOA) to obtain the optimal solution. Based on the results of the finite element analysis, the mechanical structure of the peanut seeder was optimized for lightweight design. Furthermore, response surface plots and static structural analysis were applied for validation. It turned out that the maximum stress of the optimized structure was less than the allowable stress; the weight of the frame reduced by 32.5% after optimization; and the first-order natural frequency did not coincide with the engine input speed or working speed, thus no resonance will occur. Field experiments showed that the qualified rate of row spacing was ≥96% when operating at different speeds of different types of seeders; The seeding depth operation performance was stable, with an average qualified rate of seeding depth of ≥92%; The performance of the seeders was also stable and reliable due to the lightweight prototype structure. The research outcomes can provide an effective technical reference and theoretical basis for the lightweight design of peanut seeders and for its continuous improvement as well in the future.Keywords: peanut sowing machine, multi-objective optimization, lightweight design, finite element analysis, optimizationDOI: 10.25165/j.ijabe.20231603.8211Citation: Yu Y, Diao L S, Wang D W, Wang J S, Wang X M, Tan X Z, et al. Lightweight design of peanut sowing machine frame based on finite element analysis. Int J Agric & Biol Eng, 2023; 16(3): 120–129.